International city's networks and diplomacy - Renato Balbim (Institute for Applied Economic Research (ipea), 2021)
The internationalization of cities and the constitution of a new international space of power involves a much more expressive number of cities than the usual global cities. Nowadays, dozens of international organizations are composed of regional capitals, medium, and even small cities. With diverse agendas and their own strategies of action, those organizations seek to interfere in global processes and negotiate with large corporations, multilateral organizations, and nation-states. Historically, the internationalization of cities carries strategic values such as peace, culture, and sustainability, among others discussed in this paper. More recently, the notion of the city as merchandise explains this process. Urban requalification and urban space commoditization are treated here under the conception of rugosities (Ribeiro, 2012), local and global rationality (Santos, 1995), and creative destruction (Brenner and Theodore, 2002). By hypothesis, I affirm that city internationalization is directly related to the democratic environment, degree of social participation, and local government's autonomy. The magnitude of this process is measured confronting original database research to secondary sources and illustrated using the Brazilian scenario. Additionally, a theoretical discussion proposes an innovative classification of those networks according to their constitution, composition, agendas, and spatialization. The characteristics, agents, and means of city diplomacy are debated, and the adequacy of other terms (paradiplomacy, federative diplomacy, and metrodiplomacy). In conclusion, it summarizes notes and indications of further research aiming to deepen the knowledge about this new and important agent of the world order, the city network.
Keywords: R11; R58; R38; 330; city diplomacy; cities' networks; internationalization; globalization; international agreements; geopolitics